Estimating internationally imported cases during the early COVID-19 pandemic - Tigist F. Menkir (Nature Portfolio, 2021)
Sparse testing early in the SARS-CoV-2 pandemic hinders estimation of the dates and origins of initial case importations. Here, the authors show that the main source of cases imported from China shifted from Wuhan to other Chinese cities by mid-February, especially for African locations.